2019
DOI: 10.1038/s41598-019-50986-4
|View full text |Cite
|
Sign up to set email alerts
|

Nestling carcasses from colonially breeding wading birds: patterns of access and energetic relevance for a vertebrate scavenger community

Abstract: Energy transfer is fundamental to ecosystem processes, affecting productivity and community structure. Large aggregations of colonially breeding birds are known as nutrient sources through deposition of feces, but also may deposit large quantities of energy in the form of dead nestlings. The magnitude and ecological relevance of this process to the scavenger community is poorly understood. We used trail cameras to monitor the fates of size-appropriate chicken carcasses in heron colonies in order to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…These larger sized wading birds may be better able to defend their nests from many kinds of mammalian predators and therefore may be more likely to engage in a nonobligate nest protector relationship with alligators than smaller sized herons, such as Little Blue Herons and Snowy Egrets. Smaller species of herons may have a more tightly evolved obligate facilitative relationship with alligators than their larger counterparts, which would be explained by their closely overlapping distributions in North America and supported by previous research describing a strong association between smaller Egretta herons and alligators 59 .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These larger sized wading birds may be better able to defend their nests from many kinds of mammalian predators and therefore may be more likely to engage in a nonobligate nest protector relationship with alligators than smaller sized herons, such as Little Blue Herons and Snowy Egrets. Smaller species of herons may have a more tightly evolved obligate facilitative relationship with alligators than their larger counterparts, which would be explained by their closely overlapping distributions in North America and supported by previous research describing a strong association between smaller Egretta herons and alligators 59 .…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, a facultative mutualistic nest protector relationship is known to exist between long-legged wading birds and the American Alligator ( Alligator mississippiensis ). In this positive ecological association, alligators facilitate a safer nesting location for wading birds by deterring mammalian nest predators from wading bird colonies, and alligators receive substantial energy from food in the form of fallen nestlings 58 , 59 . Wading birds are also attracted to nesting sites with alligators present 17 .…”
Section: Introductionmentioning
confidence: 99%
“…(2019) and Gabel et al . (2019) reported that vertebrates consumed most monitored carcasses (85% and 89.5%, respectively). By contrast, Abernethy et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important in aquatic ecosystems, as terrestrial scavengers often consume carrion originating from aquatic environments, such as brown bears ( Ursus arctos Linnaeus) or terrestrial arthropods feeding on salmon carcasses (Collins & Baxter, 2014; Lincoln, Wirsing & Quinn, 2021), or terrestrial vertebrate scavengers consuming common carp carcasses, the most abundant fish in many wetlands (Orihuela‐Torres et al ., 2022). To some extent, the exchange can also take place in the opposite direction when aquatic scavengers consume terrestrial subsidies such as American alligators ( Alligator mississippiensis Daudin) consuming large amounts of carrion in waterfowl breeding colonies (Gabel, Frederick & Zabala, 2019). Aquatic subsidies are of vital importance for terrestrial ecosystems, affecting all trophic levels, from primary producers (Ben‐David, Hanley & Schell, 1998; Irick et al ., 2015) to top predators (Rose & Polis, 1998; Darimont, Paquet & Reimchen, 2008; Escobar‐Lasso et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being one of the most productive ecosystems on Earth and extremely valuable for humans (Zedler & Kercher, 2005 ), studies of carrion consumption patterns in wetlands are scarce. To the best of our knowledge, the few studies carried out in wetlands monitored the consumption of bird (Gabel et al, 2019 ; Hiraldo et al, 1991 ; Linz et al, 1991 ; Pain, 1991 ), amphibian, and reptile carcasses (Abernethy et al, 2017 ), never covering more than one season.…”
Section: Introductionmentioning
confidence: 99%